Soviet strategies in Southeast Asia an exploration of Eastern policy under Lenin and Stalin - McLane, Charles B. (Princeton legacy library, 1966)
This study's main concern is with the growth of Communism within Burma, Thailand, Malaya, Indonesia, Indochina, and the Philippines. The author explores the origin and fate of these indigenous movements, their role in domestic politics and relationship to the metropolitan parties (in the case of colonial dependencies) and to the Soviet Union, and their success or failure under the conditions of independence. He also assesses the influence of Communist experience in China, the formation of Russian policy in Southeast Asia, and the policies of the domestic Communist parties.